Neurologic Features Associated With SARS-CoV-2 Infection in Children: A Case Series Report. (September 2021) - Sandoval, Francisca; Julio, Katherine; Méndez, Gastón; Valderas, Carolina; Echeverría, Alejandra C.; Perinetti, María José; Suarez, N. Mario; Barraza, Gonzalo; Piñera, Cecilia; Alarcón, Macarena; Samaniego, Fernando; Quesada-Rios, Pía; et al.
Introduction: Although multiple neurologic manifestations associated with SARS-CoV-2 infection have been described in adults, there is little information about those presented in children. Here, we described neurologic manifestations associated with COVID-19 in the pediatric population. Methods: Retrospective case series report. We included patients younger than 18 years, admitted with confirmed SARS-CoV-2 infection and neurologic manifestations at our hospital in Santiago, Chile. Demographics, clinical presentations, laboratory results, radiologic and neurophysiological studies, treatment, and outcome features were described. Cases were described based on whether they presented with predominantly central or peripheral neurologic involvement. Results: Thirteen of 90 (14.4%) patients admitted with confirmed infection presented with new-onset neurologic symptoms and 4 patients showed epilepsy exacerbation. Neurologic manifestations ranged from mild (headache, muscle weakness, anosmia, ageusia), to severe (status epilepticus, Guillain-Barré syndrome, encephalopathy, demyelinating events). Conclusions: We found a wide range of neurologic manifestations in children with confirmed SARS-CoV-2 infection. In general, neurologic symptoms were resolved as the systemic presentation subsided. It is essential to recognize and report the main neurologic manifestations related to this new infectious disease in the pediatric population. More evidence is needed to establish the specific causality of nervous system involvement.